Flavor, Lipid, and Transcriptomic Profiles of Chinese Wagyu Beef Cuts: Insights into Meat Quality Differences - Tianliu Zhang; Tingting Wang; Yanhao Gao; Jiashun Sheng; Hossam E. Rushdi; Wentao Li; Yu Sun; Tong Fu; Feng Lin; Tengyun Gao; Shenhe Liu (Foods, 2025)
This study aimed to investigate the flavor formation and meat quality differences among different beef cuts in Chinese Wagyu cattle. The metabolites and gene expression profiles of chuck, neck, rump, tenderloin, and longissimus lumborum cuts were analyzed. The results revealed that a total of 240 volatile organic compounds and 779 lipid molecules were detected among the beef cuts, with hydrocarbons (accounting for 29.71%) and triglycerides (representing 41.21%) emerging as the most prominent compounds, respectively. The sensory-directed analysis highlighted the significance of sweet and fruity aroma compounds, which contributed to the distinct aroma profiles among different beef cuts. Additionally, a total of 60 key lipid molecular markers, including FA(18:1), PC(40:5), TG(18:0_16:1_18:1), and TG(36:0_18:1), etc., were identified as playing crucial roles in the generation of essential lipid compounds across five different beef cuts. Integrative analysis of multi-omics data pinpointed a cluster of differentially expressed genes (e.g., DLD, ACADM, PCCA, SCD), which were involved in the regulation of valine, leucine, and isoleucine degradation pathways and lipid metabolism. Taken together, this study has identified key metabolites and candidate genes influencing meat quality across different beef cuts, providing a valuable resource for the molecular breeding of high-quality traits in beef cattle.